Introduction: Habit and Literature (Itinera, 2024)
Starting from antiquity, the concept of habit has traversed the entire history of Western philosophy and has represented one of the great themes of modern and contemporary literature. The reflection on habit has raised questions concerning the relationship between body and mind, the problem of time and the (re)construction of identity, the conscious and the unconscious, and the role of memory.This dossier addresses these questions from an aesthetic perspective, at the crossroads between the history of philosophy and the history of literature.
Keywords: Habit, Literature, Identity, Unconscious